Meta‐analysis of second‐trimester markers for trisomy 21. (24th January 2013) - Agathokleous, M.; Chaveeva, P.; Poon, L. C. Y.; Kosinski, P.; Nicolaides, K. H.
ABSTRACT Objective To summarize by meta‐analysis the accumulated data on the screening performance of second‐trimester sonographic markers for fetal trisomy 21. Methods We conducted a literature search to identify studies between 1995 and September 2012 that provided data on the incidence of sonographic markers in trisomy 21 and euploid fetuses at 14–24 weeks' gestation. Weighted independent estimates of detection rate, false‐positive rate and positive and negative likelihood ratios (LR) of markers were calculated. Results A total of 48 studies was included in the analysis. The pooled estimates of positive and negative LR were, respectively: 5.83 (95% CI, 5.02–6.77) and 0.80 (95% CI, 0.75–0.86) for intracardiac echogenic focus; 27.52 (95% CI, 13.61–55.68) and 0.94 (95% CI, 0.91–0.98) for ventriculomegaly; 23.30 (95% CI, 14.35–37.83) and 0.80 (95% CI, 0.74–0.85) for increased nuchal fold; 11.44 (95% CI, 9.05–14.47) and 0.90 (95% CI, 0.86–0.94) for hyperechogenic bowel; 7.63 (95% CI, 6.11–9.51) and 0.92 (95% CI, 0.89–0.96) for mild hydronephrosis; 3.72 (95% CI, 2.79–4.97) and 0.80 (95% CI, 0.73–0.88) for short femur; 4.81 (95% CI, 3.49–6.62) and 0.74 (95% CI, 0.63–0.88) for short humerus; 21.48 (95% CI, 11.48–40.19) and 0.71 (95% CI, 0.57–0.88) for aberrant right subclavian artery (ARSA); and 23.27 (95% CI, 14.23–38.06) and 0.46 (95% CI, 0.36–0.58) for absent or hypoplastic nasal bone. The combined negative LR, obtained by multiplying the values of individual markers, was 0.13 (95% CI, 0.05–0.29) when short femur but not short humerus was included and 0.12 (95% CI, 0.06–0.29) when short humerus but not short femur was included. Conclusion The presence of sonographic markers increases, and absence of such markers decreases, the risk for trisomy 21. In the case of most isolated markers there is only a small effect on modifying the pre‐test odds for trisomy 21, but with ventriculomegaly, nuchal fold thickness and ARSA there is a 3–4‐fold increase in risk and with hypoplastic nasal bone a 6–7‐fold increase. Copyright © 2012 ISUOG. Published by John Wiley & Sons, Ltd.